SEED LONGEVITY CHART TO PREDICT VIABILITY OF CORN SEED DURING OPEN STORAGE - ANDREOLI, CLAUDINEI; ANDRADE, RAMIRO VILELA DE (International Journal of Maize & Sorghum, 2010)
The simplified equation Vt = Vi – tgb.p is to predict the percentage of viability of any corn (Zea mays L.) seed lot after any period of time under open storage conditions. Based upon that equation, the objective of this work was to set a practical seed longevity chart to predict viability of corn seed lot during storage. From data of five corn seed lots stored at Sete Lagoas, MG, the value of the storage index (s) was calculated. This value (s = 120 days) corresponded exactly to the time taken in days for the initial germination of corn seeds stored to fall to a certain germination value observed in the accelerated aging test. Once the storage index (s) is estimated, the viability chart which illustrates the relationship between initial germination, seed deterioration rate and storage condition over time can be constructed. The chart can be used by any seed producer once the value of storage index (s) in situ is determined. The application of the seed viability chart to short-term seed storage seems to be promising for seed growers. This predictive model is the first attempt of incorporating the effect of seed quality, the deterioration rate and the storage environmental conditions (temperature and relative humidity) into a seed longevity chart of an open storage.